CO2 supplementation dissociates cerebral oxygenation and middle cerebral artery blood velocity during maximal cycling - Hansen, R. K.; Nielsen, P. S.; Schelske, M. W.; Secher, N. H.; Volianitis, S. (Scandinavian Journal of Medicine & Science in Sports, 2020)
This study evaluated whether the reduction of prefrontal cortex oxygenation (ScO2) during maximal exercise depends on the hyperventilation-induced hypocapnic attenuation of middle cerebral artery blood velocity (MCA Vmean). Twelve endurance-trained males (age: 25 ± 3 years, height: 183 ± 8 cm, weight: 75 ± 9 kg; mean ± SD) performed in three separate laboratory visits, a maximal oxygen uptake (VO2max) test, an isocapnic (end-tidal CO2 tension (PetCO2) clamped at 40 ± 1 mmHg), and an ambient air controlled-pace constant load high intensity ergometer cycling to exhaustion, while MCA Vmean (transcranial Doppler ultrasound) and ScO2 (NIRS) were determined. Duration of exercise (12 min 25 s ± 1 min 18 s) was matched by performing the isocapnic trial first. Pulmonary VO2 was 90 ± 6% vs. 93 ± 5% of the maximal value (P = 0.012) and PetCO2 40 ± 1 vs. 34 ± 4 mmHg (P < 0.05) during the isocapnic and control trials, respectively. During the isocapnic trial MCA Vmean increased by 16 ± 13% until clamping was applied and continued to increase (by 14 ± 28%; P = 0.017) until the end of exercise, while there was no significant change during the control trial (P = 0.071). In contrast, ScO2 decreased similarly in both trials (-3.2 ± 5.1% and -4.1 ± 9.6%; P < 0.001, isocapnic and control, respectively) at exhaustion. The reduction in prefrontal cortex oxygenation during maximal exercise does not depend solely on lowered cerebral blood flow as indicated by middle cerebral blood velocity.